The Realisation of the Refusal Speech Act in Tanjung Tanah Dialect of Kerinci - Marniati Marniati; Mohammad Fadzeli Jaafar (Masyarakat Linguistik Indonesia Universitas Andalas, 2022)
This study investigates the realisation of the refusal speech acts addressed by the native speakers of Tanjung Tanah (Tj. Tanah) dialect of Kerinci to the interlocutors of high, low and equal social status. Twenty-five native speakers of the Tj. Tanah dialect; 10 males and 15 females whose ages between 19 to 26-year-old were selected to be research participants. Data were collected by means of an open role-play. Then, the role-play’s data were transcribed and were classified according to the taxonomy of the refusal strategies formulated by Beebe, Takahashi, & Uliss-Weltz (1990). The results showed that the native speakers of Tj. Tanah dialect employed two direct strategies, fourteen indirect strategies, and four adjuncts to refusal. In addition to this, they made different frequency of the semantic formulas when declining the wish of the interlocutors of different social status. Mostly, they made higher frequency of ‘Reasons’, direct ‘No’, ‘Negative Willingness’ and ‘Elaborative Reasons’ to the interlocutors of high and low social status. In contrast, they made higher frequency of direct ‘No’, ‘Reasons’, ‘Negative Willingness’ and ‘Persuasion’ to the interlocutors of equal social status. Clearly, the social status of the interlocutors affects the participants’ choice of the refusal strategies.